Partitive mixing of colours interactive device - Veiga, Ricardo (2008)
Rotating a disk with differently coloured sectors is a well-known means of achieving partitive mixing of colours. Most educational devices applying this technique use a single motor that spins only one disk at a time, requiring different disks to be swapped between them. This paper describes an interactive device equipped with five motors, each one holding its own disk. These motors can be switched on individually, allowing more than one disk to rotate at the same time. Some fundamentals on colour mixing are introduced. A few construction details are given, too. The device, built for a science exhibition, has also been used in the classroom.